THE ROLE OF MODERN TECHNOLOGIES IN SOCIETY (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Modern technology revolutionizes the combination of computing and networking, which gives users more control over advancedequipment and the ability to use it. Modern technology could enhance the productivity and efficiency by allowing people to complete their tasks quickly. It allows consumers to assist in making better decisions and minimize the number of human errors by providing access to a greater amount of information